2020
DOI: 10.3389/fspor.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Sport Research Can Better Predict Competition Performance, Identify Individual Differences, and Quantify Task Representation

Abstract: Sport performance consists of interacting individual, task and environmental constraints, but research has used a monodisciplinary, rather than an interdisciplinary approach to understand performance. This study used Australian football (AF) as the exemplar sport to investigate the value of an interdisciplinary approach to understand sport performance. Through this, it was also possible to quantify individual differences and representative task design. Fifty-nine semi-professional Australian footballers partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…While during the resting period, only BL was significantly related with MET for the training group (QIC = 95, 95% CI = −0.003~0.000, p = 0.045*) but for the untrained group RER, HR, SBP, DBP, and RPE (QIC = 48, 95% CI = −0.024~0.422, p = 0.000*~0.002*) significantly correlated with MET (Table 4). The results of this study observed that during exercise and rest periods, the untrained group has low QIC and more significant p-values than the training group models which are more predictive as per the criteria for evaluating these models [18,20].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…While during the resting period, only BL was significantly related with MET for the training group (QIC = 95, 95% CI = −0.003~0.000, p = 0.045*) but for the untrained group RER, HR, SBP, DBP, and RPE (QIC = 48, 95% CI = −0.024~0.422, p = 0.000*~0.002*) significantly correlated with MET (Table 4). The results of this study observed that during exercise and rest periods, the untrained group has low QIC and more significant p-values than the training group models which are more predictive as per the criteria for evaluating these models [18,20].…”
Section: Discussionmentioning
confidence: 77%
“…(2) Resting models: During resting periods, group models were also computed using the same variables as explained above but the resting data for MET, RER, HR, SBP, DBP, BL, and RPE were used. The estimate (ß), standard error (SE), 95% confidence interval (CI), and p-value were considered for GEE modeling [18]. A narrower 95% CI indicates a more accurate estimate, while a wider 95% CI indicates a less accurate estimate [19].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A DoM is a method of multidisciplinary functioning that draws on the rich empirical and experiential knowledge of a group of practitioners and applied scientists in a democratic fashion (to avoid prioritising one subdiscipline over another), to attend to the fundamental relationship between theory and practice. Indeed, whilst the DoM concept was first proposed by Rothwell et al [3], there have been calls for greater disciplinary functioning within sport science for the last two decades (for example, see [6][7][8][9]). Whilst the nuances of which 'type' of disciplinary functioning fall outside of this opinion piece, Rothwell et al [3] proposed that multidisciplinarity is what could enable practitioners to draw on knowledge from different sub-disciplines, whilst remaining within the bounds of their expertise.…”
Section: A Department Of Methodologymentioning
confidence: 99%
“…Thirdly, even though we utilised a multidimensional testing battery, other approaches to assessment potentially useful in basketball settings were not incorporated into our study. For example, there has been an increased call for in-situ tasks and stronger ecological validity within assessments selected in TID processes [47]. Consequently, development of testing protocols assessing performance during small-sided games or in-situ tasks where match skills can be directly quantified or rated may be useful to explore in future basketball research on this topic.…”
Section: Plos Onementioning
confidence: 99%